Literacy Conditions of Reading, Writing and Calculating for Elementary School Students - Khofifah, Siti; Ramadan, Zaka Hadikusuma (Journal of Education Reseach and Evaluation, 2021)
The lack of interest in students in reading and writing had a low impact on literacy culture, caused by a lack of awareness of parents at home to accompany the learning process and a lack of teacher commitment in the GLS education resulting in low skin of learners. This study aimed to analyze the basic literacy (reading, writing, and numeracy) of elementary school children. The type of research used in this study was qualitative descriptive research.  The data collected was obtained from the principal and three teacher homeroom methods of interviewing, observation, and documentation studies. This study used analysis techniques from Miles, and Huberman described which consists of 1)  Data  Collection; 2)  Data  Reduction; 3)  Data  Display; and 4)  Conclusion drawing/verification.   The results showed that some indicators had not been implemented 100% in basic literacy planning, caused by time problems in implementing literacy activities, reduced collection materials in the classroom at the end of the semester, and reduced teacher commitment to implementing reading habituation classroom. So,  the literacy condition had not been running optimally. This can be seen from several factors that have not been implemented, such as the number of visits to the library, the number of collections supporting the GLS program. GLS constraints were the implementation time, inadequate collection amount, and lack of teacher commitment in applying literacy. Given that Literacy capability becomes a very important aspect in producing good competitiveness, this should be noted.